ANALYSIS OF SURVIVAL DATA FOR BREAST CANCER PATIENTS: A CASE STUDY ASSUMING CURE FRACTION MODELS UNDER THE BAYESIAN APPROACH - ICUMA, Tatiana Reis; BUZATTO, Isabela Panzeri Carlotti; TIEZZI, Daniel Guimarães; ACHCAR, Jorge Alberto (Brazilian Journal of Biometrics, 2016)
Breast cancer is the second most common cancer in the world (WORLD CANCER REPORT 2014 a, b). The evolution of the treatment of breast cancer allows a longer life for the patients. In this article, it will be considered a study with a data set related to a study conducted at the Hospital das Clinicas, Faculty of Medicine, University of São Paulo, Ribeirão Preto, Brazil, with patients in stages II and III of HER2 breast cancer treated at the HCFMRP USP breast cancer division from 2008 to 2012, undergoing neoadjuvant chemotherapy combined with Herceptin drug. The aim of this study is to verify that there are significant differences in survival times of patients who received at least four cycles of Herceptin. As a secondary objective, it will be checked if some observed covariates (age,  stage of disease, type of surgery, pathologic complete response, positive for estrogen receptor or positive for receptor have significant effects on the patients survival times (SLD: free survival disease and ST: overall survival, both in months) for this, we discuss the advantages of a statistical cure fraction model in terms of fit to the data when compared with traditional models based on the Weibull distribution without cure fraction under an classical or a Bayesian approach where a comparative study.